M. Arsyad Al-Banjari (Pejuang dan Penyebar Islam di Kalimantan) - Barsihannor Barsihannor (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2010)
Islam had been spread out in South Kalimantan 180 years before M. Arsyad al-Banjari was born. It slowly developed because there is no ulama who pionered the Islamic development and spreading. Morever Islam in that time was aculturated with local culture due the most people adhered Hindu, anismism, dynamism and “kaharingan”. This former religion or ism very influenced and coloured social life. It was reflected in their daily life. Observing this fact. Al-Banjari feels responsible on this situiation. He made effort to improve the belief and ritual practice in Moslem community by spreading Islamic mission. Some ways were implemented among others; making Majelis Ta’lim, writing books, preaching and cadre preparation